Cation‐Selective Separators for Addressing the Lithium–Sulfur Battery Challenges. Issue 3 (16th December 2020) - Zhao, Qing; Hao, Zhendong; Tang, Jiadong; Xu, Xiaolong; Liu, Jingbing; Jin, Yuhong; Zhang, Qianqian; Wang, Hao
Abstract: Lithium–sulfur batteries (LSBs) have become one of the most promising candidates for next‐generation energy storage systems owing to their high theoretical energy density, environmental friendliness, and cost effectiveness. However, real‐word applications are seriously restricted by an undesirable shuttle effect and Li dendrite formation. In essence, uncontrollable anion transport is a key factor that causes both polysulfide shuttling and dendrite formation, which creates the possibility of simultaneously addressing the two critical issues in LSBs. An effective strategy to control anion transport is the construction of cation‐selective separators. Significant progress has been achieved in the inhibition of the shuttle effect, whereas addressing the problem of Li dendrite formation by utilizing a cation‐selective separator is still under way. From this viewpoint, this Review analyzes critical issues with regard to the shuttle effect and Li dendrite formation caused by uncontrollable anion transport, based on which roles and advantages of cation‐selective separators toward high‐performance LSBs are presented. According to the separator‐construction principle, the latest advances and progress in cation‐selective separators in inhibiting the shuttle effect and Li dendrite formation are reviewed in detail. Finally, some challenges and prospects are proposed for the future development of cation‐selective separators. This Review is anticipated to provide a new perspective for simultaneously addressing the two critical issues in LSBs. Abstract : Cation‐selective separator : In this Review, the latest advances and progress in the construction of cation‐selective separators for addressing two critical issues regarding shuttle effect and lithium dendrites in lithium‐sulfur batteries (LSBs) are ummarized in detail, according to the three main design strategies. These include size confinement, electrostatic interactions, and adsorption effects. Then several perspectives on the future development of cation‐selective separators for constructing high‐performance LSBs are proposed.